Peran Kualitas Pelayanan Dalam Memediasi Pengaruh Harga Terhadap Kepuasan Tamu Menginap Di Hotel Mersi Bukittinggi - Fajarwati, Khafifah; Abrian, Youmil; Andres, Fran Serano (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
This research is based on the background based on the response of visitors to the Mersi Bukittinggi hotel which can be seen from the slow response to guests at check-in and chek out, getting complaints from guests because the room booked is not as desired, high room prices during high season. The purpose of this study was to determine the effect of price on guest satisfaction with service quality as a mediating variable at Hotel Mersi Bukittinggi. The population in this study amounted to 698 people and the research sample amounted to 88 people. The data collection technique used a questionnaire with a Likert scale. The data analysis technique consists of descriptive data, path analysis and hypothesis testing. The results of the study describe that price has a direct effect on guest satisfaction, descriptively that the price is in the good category with an achievement rate of 45.4%. Price has a direct effect on service quality seen from the value of t count> t table (2.627> 1.67).